2002
DOI: 10.1159/000051999
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Interleukin-2 Receptor as a Predictor of Lymph Node Metastasis in Early Gastric Cancer

Abstract: Background: In the present study, we investigated the clinical significance of serum soluble IL-2R as a predictor of lymph node metastasis in patients with early gastric cancer. Patients and Methods: Seventy-four patients with early gastric cancer were enrolled in this study. Levels of serum soluble IL-2R were measured by an enzyme-linked immunosorbent assay. Result: Significant differences in serum soluble IL-2R between the control group and cases of T1 were not recognized. On the other hand, levels of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Therefore, serum sIL-2R is often measured as a substitute for IL-2, since it reflects the activity of IL-2 by attaching to its receptor as an autocrine, and it is easy to detect because of its relative stability in the serum. 30 Several investigators have reported recognizing elevated levels of sIL-2R in patients with various malignant disorders, [30][31][32] and some reports describe the relationship between IL-12 and sIL-2R in other clinical conditions. In acute graft-versus-host disease after allogenetic bone marrow transplantation, the serum IL-12 and sIL-2R levels increased simultaneously 33 and patients with immune arthropathy had increased IL-12 and sIL-2R levels in the synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, serum sIL-2R is often measured as a substitute for IL-2, since it reflects the activity of IL-2 by attaching to its receptor as an autocrine, and it is easy to detect because of its relative stability in the serum. 30 Several investigators have reported recognizing elevated levels of sIL-2R in patients with various malignant disorders, [30][31][32] and some reports describe the relationship between IL-12 and sIL-2R in other clinical conditions. In acute graft-versus-host disease after allogenetic bone marrow transplantation, the serum IL-12 and sIL-2R levels increased simultaneously 33 and patients with immune arthropathy had increased IL-12 and sIL-2R levels in the synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Li Ling et al (13) demonstrated that high sIL-2R serum levels were significantly decreased following removal of the tumors. Tartour et al (14), Murakami et al (15) and Grotowski and Piechota (16) reported that the sIL-2R serum levels of head and neck, gastric and colorectal cancer patients were significantly higher compared to the control groups and showed an increase with progression of clinical stage. Lai et al (17) revealed that sIL-2R serum levels in nasopharyngeal carcinoma patients were significantly higher compared to the normal controls and was significantly increased with progression of clinical stage, with stage III-IV>I-II sIL-2R serum levels being lower subsequent to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Murakami et al [18] study serum IL-2Rα level can predict lymph node metastasis in early gastric cancer regardless of cell differentiation. However based on the results of our study, only the serum IL-2Rα level in undifferentiated type were different according to lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%